Growth of Banggai Cardinalfish Pterapogon kauderni Reared at Different Salinity in a Controlled System - . Madinawati; Samliok Ndobe; Afiat Gamgulu (Jurnal Akuakultur Indonesia)
The research was conducted to study the effect of salinity on the growth of Banggai Cardinalfish Pterapogon kauderni. The research was set up in completely randomized design with different salinity as the main variable, i.e. 27, 29, 31, 33 and 35 ppt with 4 replications. The result showed that the lowest salinity (27 ppt) resulted in the highest fish growth (1.625 g).